2014
DOI: 10.1111/cts.12194
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Translation Gap in Child Health Exercise Research: A Call for Disruptive Innovation

Abstract: In children, levels of play, physical activity, and fitness are key indicators of health and disease and closely tied to optimal growth and development. Cardiopulmonary exercise testing (CPET) provides clinicians with biomarkers of disease and effectiveness of therapy, and researchers with novel insights into fundamental biological mechanisms reflecting an integrated physiological response that is hidden when the child is at rest. Yet the growth of clinical trials utilizing CPET in pediatrics remains stunted d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…CPET biomarkers are used to assess disease severity, progress, and response to therapy (including exercise prescriptions) across an expanding range of childhood diseases and conditions and across the lifespan (Ploeger et al, 2009;Pahkala et al, 2013;Liem et al, 2015;Sule and Fontaine, 2016;Cordingley et al, 2016;Gualano et al, 2017;Li et al, 2017). Despite these factors, CPET has failed to fulfil its promise in child health research and clinical practice (Ashish et al, 2015). A major barrier to more accurate and effective clinical use of CPET in children and adults has been a lack of harmonization of protocol types and exercise modalities (Ashish et al, 2015), factors that influence CPET results (Fredriksen et al, 1998;Beltrami et al, 2012;Bires et al, 2013;May et al, 2014;Cunha et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CPET biomarkers are used to assess disease severity, progress, and response to therapy (including exercise prescriptions) across an expanding range of childhood diseases and conditions and across the lifespan (Ploeger et al, 2009;Pahkala et al, 2013;Liem et al, 2015;Sule and Fontaine, 2016;Cordingley et al, 2016;Gualano et al, 2017;Li et al, 2017). Despite these factors, CPET has failed to fulfil its promise in child health research and clinical practice (Ashish et al, 2015). A major barrier to more accurate and effective clinical use of CPET in children and adults has been a lack of harmonization of protocol types and exercise modalities (Ashish et al, 2015), factors that influence CPET results (Fredriksen et al, 1998;Beltrami et al, 2012;Bires et al, 2013;May et al, 2014;Cunha et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these factors, CPET has failed to fulfil its promise in child health research and clinical practice (Ashish et al, 2015). A major barrier to more accurate and effective clinical use of CPET in children and adults has been a lack of harmonization of protocol types and exercise modalities (Ashish et al, 2015), factors that influence CPET results (Fredriksen et al, 1998;Beltrami et al, 2012;Bires et al, 2013;May et al, 2014;Cunha et al, 2015). For example, in clinical trials involving CPET in children over the past five years, a PubMed search revealed 40 published studies that used CE and 113 that used TM.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing aerobic fitness in pediatric populations, typically using CPET, has been shown to have substantial discrepancies with lack of common terminology, standard protocols, and calibration (4). Measuring aerobic fitness in children is complicated because muscle and fat mass and hormonal regulation of metabolism and growth change rapidly in children and adolescents (32;53;108).…”
Section: Obstacles In Identifying the Gaps Of Knowledge; Linking Obesmentioning
confidence: 99%
“…It will not only facilitate the large-scale studies required to advance pediatric care, but will also ultimately lead to the establishment of true, nationally representative, normative data for children’s physiological response to exercise. The Data Harmonization in Exercise Data study group has identified a strategy and direction for achieving data harmonization which can be accomplished by carefully examining exercise data as well as data collection and reporting protocols for peak data from multiple institutions [ 56 ].…”
Section: Discussionmentioning
confidence: 99%